1988
DOI: 10.1080/00480169.1988.35471
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of macroscopic sarcocysts in New Zealand cattle at slaughter

Abstract: A survey carried out to determine the prevalence of visible Surcocystis spp. infection in 100 slaughtered cattle in a South Island abattoir revealed 64% infected. Although all ages, genders, breeds and export grades were infected, only host age had a statistically significant effect on the infection rate. Infections were most common in the rectus abdominis and the psoas muscles (47% and 41% respectively). Most infections were light, with less than ten macrocysts seen, though infections of more than 50 macrocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Most of the sarcocysts found in carcases are small and slender, averaging about 4 mm long, and can be difficult to see; in any case, most sarcocysts are within the muscle and not visible on its surface; most infections are light; the practicalities of meat inspection are that relatively little time can be spent examining each animal. In a study in which the tongue, heart, diaphragmatic crurae, and oesophagus were examined each for 1 min, and a further 20 min spent examining half the carcase, Mitchell (1988) found 64 of 100 cattle infected, but in 78% of these <20 cysts could be found. Detecting such low levels at routine meat inspection is virtually impossible.…”
Section: Sarcocystis Speciesmentioning
confidence: 99%
“…Most of the sarcocysts found in carcases are small and slender, averaging about 4 mm long, and can be difficult to see; in any case, most sarcocysts are within the muscle and not visible on its surface; most infections are light; the practicalities of meat inspection are that relatively little time can be spent examining each animal. In a study in which the tongue, heart, diaphragmatic crurae, and oesophagus were examined each for 1 min, and a further 20 min spent examining half the carcase, Mitchell (1988) found 64 of 100 cattle infected, but in 78% of these <20 cysts could be found. Detecting such low levels at routine meat inspection is virtually impossible.…”
Section: Sarcocystis Speciesmentioning
confidence: 99%
“…Many reports on the prevalence of ovine Sarcocystis species have revealed that sarcosporidiosis is still an extremely common infection even in developed countries (Savini et al 1992). The parasites of genus Sarcocystis are among the most commonly found parasites in domestic ruminants and some species of Sarcocystis can generate important economic loss when causing clinical and subclinical disease (Mitchell 1988). Pigs with heavy infections of 40 Sarcocystis or more per gram of diaphragm showed symptoms of weakness of loins, muscular stiffness, and temporary posterior paralysis.…”
Section: Introductionmentioning
confidence: 99%
“…Heart, diaphragm, and skeletal muscles are the preferred organs for Sarcocystis spp. location in the intermediate host and can persist through life in the hosts but many start to disappear after three months of inoculation (Mitchell 1988). Meat that is heavily infected may be condemned as unfit for human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports on the prevalence of ovine Sarcocystis species have revealed that sarcosporidiosis is still an extremely common infection even in developed countries (Savini et al 1992). The parasites of genus Sarcocystis are among the most commonly found parasites in domestic ruminants and some species of Sarcocystis can generate important economic loss when causing clinical and subclinical disease (Mitchell 1988;Silva et al 2002). Pigs with heavy infections of 40 Sarcocystis spp.…”
Section: Introductionmentioning
confidence: 99%
“…Heart, diaphragm, and skeletal muscles are the preferred organs for Sarcocystis spp. location in the intermediate host and can persist through life in the hosts but many start to disappear after three months of inoculation (Mitchell 1988). Meat that is heavily infected may be condemned as unfit for human consumption (Olsen 1974).…”
Section: Introductionmentioning
confidence: 99%